Effect of enterogermina (Bacillus clausii spores) on the productive performance of broilers - Núñez Torres, Oscar (2017)
The effect of a commercial probiotic, Enterogermina (Bacillus clausii spores) in the drinking water on the productive performance of broilers was evaluated. A total of 280 male broilers, Cobb line, of one day of age were used for 49 days. The chicks were distributed in four treatments with seven replicates per treatment: T0 = balanced feed (control), T1, T2 and T3 = balanced feed + 0.25, 0.50 and 0.75 ml of enterogermina per liter of water, respectively, in a randomized complete block design. T2 showed a better body weight gain (2973 g) as compared to T0, T1 and T3 (2627, 2687 and 2831 g, respectively) (p<0.05). Feed intake was similar between treatments (from 6102 to 7084 g/bird); however, T2 obtained the best feed conversion (2.02, p<0.05) and higher carcass yield (75.3%) than the other treatments. The economic analysis reported a profitability of 25.84% for T2, compared with 0.19, 8.21 and 15.44% for T0, T1 and T3, respectively. It is concluded that the application of enterogermina in doses of 0.50 ml/l of drinking water improves the productive performance and economic return in broilers.